The Development of Higher Education for Women in the United States: The 1958 National Defense Education Act (NDEA) - Liu, Yanlin (Journal of Education and Educational Technologies, 2023)
In 1958, the United States, under various pressures, promulgated the renowned National Defense Education Act (NDEA). This multifaceted legislation encompassed all levels of education, from elementary to higher education, and had far-reaching implications. However, few have recognized the significant contribution of this act in advancing gender equality for American women. Data reveals that following the enactment of the NDEA, more women gained access to higher education, entered the workforce, and pursued various professions, thus directly or indirectly propelling the cause of gender equality for American women.